CRITTICAL JURNAL REVIEW KATA BAKU DAN TIDAK BAKU - Fadilla Albi Harahap; Usiono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The widespread use of standard and non-standard languages ​​among society is very problematic. Many members of society, especially students or the millennial generation, make mistakes in pronouncing it incorrectly. This research is library research, namely a series of research related to library data collection methods, or research whose research objects are traced and explored through various library information through (books, encyclopedias, scientific journals, newspapers, magazines and documents. Data used in this research is secondary data. Secondary data is data obtained not from direct observation but rather the data is obtained from the results of research conducted by previous researchers related to use standard word.